Development of a multi-epitope vaccine candidate to combat SARS-CoV-2 and dengue virus co-infection through an immunoinformatic approach - Mandal, Saurav; Chanu, Waribam Pratibha; Natarajaseenivasan, Kalimuthusamy (Frontiers in Immunology, 2025)
BackgroundAlthough the SARS-CoV-2 and dengue viruses seriously endanger human health, there is presently no vaccine that can stop a person from contracting both viruses at the same time. In this study, four antigens from SARS-CoV-2 and dengue virus were tested for immunogenicity, antigenicity, allergenicity, and toxicity and chosen to predict dominant T- and B-cell epitopes.MethodsFor designing a multi-epitope vaccine, the sequences were retrieved, and using bioinformatics and immunoinformatics, the physicochemical and immunological properties, as well as secondary structures, of the vaccine were predicted and studied. Additionally, the three-dimensional structure was estimated, improved upon, and confirmed using bioinformatics methods before being docked with TLR-2 and TLR-4. Eight helper T-cell lymphocyte (HTL) epitopes, ten cytotoxic T-cell lymphocyte (CTL) epitopes, nine B-cell epitopes, and TLR agonists were used to create a new multi-epitope vaccine. Furthermore, according to the immunological stimulation hypothesis, the vaccine could stimulate T and B cells to create large quantities of Th1 cytokines and antibodies.ResultsThe study indicates that the developed vaccine is a favorable vaccine candidate with antigenicity, immunogenicity, non-toxicity, and non-allergenicity properties. The vaccine construct was made up of 460 amino acids, had an MW of 49391.51 Da, a theoretical pI of 9.86, and the formula C2203H3433N643O618S18, a lipid index of 39.84, a GRAVY of −0.473, an aliphatic index of 63.80, and an instability index of 39.84, which classifies the protein to be stable.ConclusionThe acquired data showed that both vaccine designs had a considerable chance of preventing the co-infection of SARS-CoV-2 and dengue virus and that they demonstrate good results following in-silico testing. Furthermore, the vaccine may be an effective strategy in preventing SARS-CoV-2 and dengue since it can cause noticeably high levels of Th1 cytokines and antibodies.